Relative Efficiency of Bonds and Sukuk: A Case of Selected Islamic Countries - Nihal, Hafiz M. Sarfraz; Hasan, Syed Shabib Ul; Majeed, Imran (iRASD Journal of Economics, 2023)
This study compares the efficiency of bonds and Sukuk through a comprehensive analysis using descriptive statistics and regression techniques. The dataset includes outstanding Sukuk and bonds issued between 1993 and 2023 in Malaysia, Indonesia, Pakistan, Turkey, and Saudi Arabia. Objectives focus on examining mean coupon rate and yield-to-maturity (YTM) differences, exploring yield variations, and assessing efficiency levels. The analysis employs t-tests and ordinary least squares (OLS) regression. Findings indicate that bonds and Sukuk are sold at a premium, with mean coupon rates exceeding YTMs. A separate analysis supports the hypothesis that Sukuk may have higher mean YTMs and coupon rates than bonds. Sukuk exhibits significantly higher YTMs, indicating greater returns compared to bonds across the selected countries. Sukuk also demonstrates higher efficiency, reflected by a positive and significant coefficient, implying a more efficient yield-to-tenure ratio. Policy implications highlight the need to enhance regulation quality and transparency in disclosing yield differentials and risks and promote Sukuk as an attractive investment option. Diversifying investment portfolios and improving market liquidity is also recommended. Limitations include limited data availability, preventing analysis of individual countries and segregation between corporate and sovereign issues within Sukuk. In conclusion, this study provides valuable insights into the efficiency of bonds and Sukuk, offering policy recommendations. Disparities in mean coupon rates, YTMs, and efficiency levels underscore the importance of informed decision-making. Policymakers and investors can utilize these findings to understand the potential benefits of Sukuk and implement strategies to foster a more efficient and robust market. Further research is necessary to address data limitations and explore specific country-level dynamics and Sukuk classifications.